2020
DOI: 10.1186/s41021-020-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine attenuates global genomic DNA methylation by influencing DNMTs gene expression in human endometrial stromal cells

Abstract: Background: There is increasing evidence indicating an incidence of infertility and also the risk of endometrial cancers among smokers. However, the mechanism underlying nicotine adverse effect on female reproduction remains unclear. Growing evidence has suggested that environmental exposures such as nicotine could modulate the epigenome. No study has yet been published to evaluate the direct effect of nicotine on the epigenome profiling of human endometrial stromal cells (HESC). Herein, we decided to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
3
0
1
Order By: Relevance
“…Sahin et al indicated that smoking has decreased the expression of CXCL-12 and FGF2 [6]; our study con rmed their results and showed that nicotine exposure can decrease the expression of CXCL-12 and FGF2 genes. Furthermore, another study demonstrated that treatment of endometrial stromal cells with nicotine at concentrations of 10 − 11 µM, 10 − 8 µM, and 10 − 6 µM for 24 h results in decreased expression of DNA methyl-transferases (DNMTs) and decreases global genomic DNA methylation levels, which con rms our results [64].…”
Section: Resultssupporting
confidence: 88%
“…Sahin et al indicated that smoking has decreased the expression of CXCL-12 and FGF2 [6]; our study con rmed their results and showed that nicotine exposure can decrease the expression of CXCL-12 and FGF2 genes. Furthermore, another study demonstrated that treatment of endometrial stromal cells with nicotine at concentrations of 10 − 11 µM, 10 − 8 µM, and 10 − 6 µM for 24 h results in decreased expression of DNA methyl-transferases (DNMTs) and decreases global genomic DNA methylation levels, which con rms our results [64].…”
Section: Resultssupporting
confidence: 88%
“… 40 42 Nicotine could attenuate DNA methylation by regulating the expression of DNMTs in human endometrial stromal cells. 43 However, previous studies commonly explored solo types of epigenetic modifications. In our study, we systematically investigated the smoking-related DNA methylation, lncRNA, and miRNA in bladder cancer, and identified 1078 DNA methylations, 506 lncRNAs, and 102 miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking further modulates the epigenomic landscape at different levels. First, tobacco constituents such as nicotine may alter the levels of selected DNMTs, including the downregulation of DNMT3A and DNMT3B [88] and the upregulation of DNMT1 [89]. Second, carcinogens in cigarette smoke such as nitrosamines or formaldehyde can damage DNA by introducing double strand breaks, which is a main cause of mutations.…”
Section: Smoking and Other Environmental Factorsmentioning
confidence: 99%